2010
DOI: 10.1189/jlb.0210097
|View full text |Cite
|
Sign up to set email alerts
|

Death induction by CD99 ligation in TEL/AML1-positive acute lymphoblastic leukemia and normal B cell precursors

Abstract: Our study was performed to examine the role of CD99 in normal and leukemia BCPs. CD99 is strongly expressed by certain pediatric cancers including BCP-ALL. Modulation of the antigen in ETs and T cells induces apoptosis, hence implicating CD99 as a potential target for anti-cancer therapy. However, nothing is known about these aspects in BCPs. We investigated BCP-ALL cases and normal BCP cells from pediatric BM for CD99 protein and RNA expression as well as for effects of CD99 modulation by mAb. Immunophenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…In contrast, when normal mesenchymal stem cells were transfected with EWS-FLI1, their susceptibility to CD99 ligation increased and p53 was reactivated. Similarly, c/pre-B leukemia blasts carrying the TEL/AML1 chimera were found to be more sensitive to CD99-induced cell death (44). These findings indicate that rapid and massive CD99-induced cell death may occur preferentially in an aberrant genetic background, when cells being forced to grow by oncogenetic stimuli could not recover stressful signals through cell-cycle exit and result more vulnerable, thus offering new fuel to support the therapeutic use of anti-CD99 dAbd C7 against EWS cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when normal mesenchymal stem cells were transfected with EWS-FLI1, their susceptibility to CD99 ligation increased and p53 was reactivated. Similarly, c/pre-B leukemia blasts carrying the TEL/AML1 chimera were found to be more sensitive to CD99-induced cell death (44). These findings indicate that rapid and massive CD99-induced cell death may occur preferentially in an aberrant genetic background, when cells being forced to grow by oncogenetic stimuli could not recover stressful signals through cell-cycle exit and result more vulnerable, thus offering new fuel to support the therapeutic use of anti-CD99 dAbd C7 against EWS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CD99 expression disappeared in tumors that were efficiently inhibited by dAbd C7. A possible bystander effect of anti-CD99 approaches is the induction of the HSP70 that may activate NK cells cytotoxicity contributing to tumor elimination (44). To verify any possible involvement of this pathway in the efficacy of anti-CD99 therapy, we have assessed whether CD99 ligation induced HSP70 S6).…”
Section: Combination With Doxorubicin Increases Dabd C7 Therapeutic Amentioning
confidence: 99%
“…The signaling mechanism of human CD99 is still unknown, despite the numerous studies describing its roles in various cellular responses, such as transmigration of leukocytes and activation, proliferation, and apoptosis of lymphocytes (22,(45)(46)(47)(48). In this study, we showed that CD99-derived agonistic ligands function as novel suppres- sors of fibronectin-mediated ␤1 integrin activation in human breast carcinoma cells and uncovered for the first time the underlying mechanism by which CD99 regulates ␤1 integrin activity.…”
Section: Discussionmentioning
confidence: 79%
“…CD99 is implicated in multiple cellular responses, including cell apoptosis, differentiation, transport of membrane proteins, and activation and proliferation of lymphocytes (18)(19)(20)(21)(22)(23). The physiological significance of CD99 engagement has been clearly shown by an essential role for CD99 in the regulation of the transendothelial migration (TEM) of immune cells (24)(25)(26).…”
mentioning
confidence: 99%
“…An additional role of mCD99, implication in cell death, has been reported; mCD99 + cells were killed through the recognition of mCD99 by PILRb-expressing NK cells (39), and the ligation of mCD99 to the polymeric fusion protein PILR-FC induced apoptosis in immature thymocytes (40), as is implicated in apoptosis of thymocytes by hCD99 (41), Ewing sarcoma cells (42,43), and lymphoblast leukemia cells (44). Given the physiologic heterodimeric and homodimeric forms of mCD99, therefore, the identity of CD99 family dimers dominant on the cell surface under normal physiological conditions, during inflammation-induced diapedesis, or during apoptosis would be necessary to be defined to understand the biological relevance of CD99 oligomerization and, ultimately, the role of CD99 protein, and this is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%